Hematological analysis of alpha-thalassemia: A single-center, retrospective clinical study - Lin Zheng; Nuolan Yin; Meiying Wang; Hailong Huang; Na Lin; Shuyu Zhang; Linjuan Su; Liangpu Xu (PLoS ONE, 2025)
Objectives To determine the optimal cutoffs of the three indicators (MCV, MCH and HbA2) for alpha-thalassemia screening and to evaluate the validity of these indicators in Fujian Province, China. Methods We conducted a retrospective analysis on the results of specimens received from May 2016 to April 2023. Receiver operating characteristic (ROC) curves were used to confirm the optimal cutoffs of the screening indicators. And the effectiveness of different combined screening methods was evaluated in patients with and without alpha-thalassemia. Results The optimal cutoffs of MCV, MCH, and HbA2 were 77.85, 27.05 and 2.55, respectively. Among them, the area under the ROC curve of MCH was 0.912, and it was the best of the three parameters used for alpha-thalassemia screening. Conclusions The results can help clinicians and laboratory technicians perform genetic counseling and prenatal diagnosis for patients. It also provide a reference for alpha-thalassemia genotype distributions in our region and the optimal cutoff values of MCV, MCH and HbA2.